KEHILANGAN HASIL PADA PENGERINGAN DAN PENGGILINGAN GABAH DI MINAHASA - Claudia Ruaw; Frans Wenur; Douwes D. Malik; Handry Rawung (COCOS, 2013)
ABSTRACTThe main problem in the post-harvest handling of paddy that often facing by the farmers is the high value of looses during post harvest. The looses occur when the paddy grains scattered during harvest or post harvest handling. This study aimed to calculate the losses of paddy grains during drying and milling in Minahasa Region. The research was conducted in Karondoran village, the east part of Langowan, Tolok village of Tompaso and in the Post Harvest Laboratory, Faculty of Agriculture, Sam Ratulangi University for 3 months. The drying looses was determined by the weight and the moisture content of the paddy samples before and after the drying process. While the looses during milling was determined by comparing the rendemen of millling and the milling yield generated in the laboratory. The result indicated that the average looses of drying in Minahasa was 2,19% while the average looses of milling in Minahasa was 2,12%.Keywords : drying, milling, looses